Ethnopharmacological usage of medicinal plants in genitourinary infections by residents of Chapada do Araripe, Crato, Ceará - Brazil - Dayanne Rakelly de Oliveira; Francisco Elizaudo de Brito Júnior; Larissa Alves Sampaio; Jamille Cansanção Torres; Andreza Guedes Barbosa Ramos; Alaiane Abreu Nunes (Universidade de Fortaleza, 2012)
Objective: To determine the ethnopharmacological use of plants in the treatment of urogenital tract infections (UTIs) by women living in the city of Crato, located in Chapada do Araripe, in the interior of the State of Ceará, Brazil. Methods: A cross-sectional study, with a quantitative approach, performed from September to November, 2010, with 25 residents of Chapada do Araripe, who use and/or recommend plants for the treatment of UTIs. Results:The prevalent characteristics of the informants were: age-group between 56 and 60 years old, married, all of them farmers with a monthly income of minimum wage, and most of them with incomplete schooling. Nine plant species were identified as being used by the population against infection, inflammation and pain. The most common forms of usage are the decoction, cooking and the maceration of leaves and barks. Barbatimão and mallow were the most reported species by informants. Conclusion: Popular medicine is greatly adopted by traditional communities and represents an incalculable cultural wealth which should be preserved and evaluated to assure sustainable development. Information brought out by this research may be useful in further pharmacological studies.